Listening to motivational music mitigates heat-related reductions in exercise performance - English, T.; Mavros, Y.; Jay, O. (Physiology & Behavior, 2019)
Purpose: To examine whether listening to motivational music mitigates heat-related reductions in exercise performance, and leads to a greater increase in thermal and cardiovascular strain. Methods: Twelve participants (26 ± 5 y, 77.5 ± 17.0 kg, 49 ± 8 ml·min-1·kg-1) completed 30-min of cycling preload at 50% VO2max followed by a 5-min rest and 15-min cycling time trial on seven separate occasions; three familiarisation sessions in a 20 °C room and four experimental trials in a climatic chamber regulated at either 21 °C, 50%RH (NEU) or 36 °C, 50%RH (HOT), each with and without the participant listening to self-selected motivational music during the 5-min rest and 15-min time trial. Measures of total work, core temperature and heart rate and blood pressure (from which rate-pressure product for cardiovascular strain was calculated), were recorded. Results: Without music, total work was lower (p < .001) in the HOT condition (168 ± 59 kJ) relative to the NEU condition (193 ± 60 kJ). With music, total work was greater relative to no music in both the NEU condition (203 ± 60 kJ vs 193 ± 60 kJ; p = .008) and HOT condition (183 ± 63 kJ vs 168 ± 60 kJ; p = .029). The greater total work in the HOT condition with music relative to no music resulted in a higher (p = .006) core temperature (38.7 ± 0.4 °C vs 38.6 ± 0.5 °C) and a higher (p < .001) rate-pressure product (34.8 ± 7.1 mmHg·beats·min-1·10-3 vs 27.8 ± 3.7 mmHg·beats·min-1·10-3). Conclusion: Listening to motivational music mitigated heat-related reductions in exercise performance with an improvement in performance in the heat of ~10%. This improved exercise performance led to a greater increase in thermal and cardiovascular strain in the heat but did not exceed levels typically associated with an elevated health risk in a young, healthy population.